UV light irradiation improves the aggregation and settling performance of metal sulfide particles in strongly acidic wastewater. (15th October 2019) - Peng, Xianjia; Xia, Zhilin; Kong, Linghao; Hu, Xingyun; Wang, Xianliang
Abstract: Tiny metal sulfide particles are usually generated in the metal sulfide precipitation process, and residual dissolved sulfide (H2 S, HS − and S 2− ) generally makes the aggregation and settling performance of these particles worse. In this work, under strongly acidic conditions with 0.102 M H2 SO4, the characteristics of CuS, CdS and mixed metal sulfide particles (CuS and CdS) produced in strongly acidic wastewater by H2 S were initially studied. Then, UV light irradiation was employed to improve the aggregation and settling performance of the metal sulfide particles, and relevant mechanisms were investigated. The results showed that the residual H2 S in suspension can deteriorate the settling performance of metal sulfide particles. After H2 S was removed, CuS particles exhibited good settling performance, but the settling performance of CdS and mixed sulfide particles remained poor. Subsequent studies showed that UV light irradiation effectively improved the aggregation and settling performance of CdS and mixed metal sulfide particles in the presence of H2 S. After 30 min of UV irradiation, the average hydrodynamic diameter of CdS particles increased approximately 166-fold in the presence of 131.40 mg/L H2 S, and that of mixed sulfide particles increased approximately 105-fold with the existence of 129.30 mg/L H2 S. Further study revealed that H2 S in suspensions played an important role in the aggregation of metal sulfide particles under UV irradiation. HS generated by the photolysis of H2 S oxidized a portion of S 2− on the surface of CdS particles and a portion of S 2− and Sn 2− on the surface of mixed sulfide particles to S2 2− and S 0, which resulted in a decrease of negative charge and an enhanced aggregation of these particles. Finally, this study showed that the settling performance of CdS and mixed sulfide particles was effectively improved at high initial H2 S concentrations under UV irradiation. This study provides a clean and effective method to improve the metal sulfide precipitation process for strongly acidic wastewater treatment. Graphical abstract: Image 1 Highlights: H2 S made aggregation and settling performance of metal sulfide particles worse. UV light enhanced aggregation of metal sulfide particles in the presence of H2 S. H2 S played a key role in UV light-induced aggregation of metal sulfide particles. UV light improved metal sulfides settling performance at high H2 S concentration.